AML Berbasis AI: Kepatuhan Cerdas atau Ancaman HAM Tersembunyi? - Makmur, Kartini Laras (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
Artificial intelligence (AI) is increasingly used by banks to detect and prevent money laundering; however, the adoption of AI-based anti-money laundering (AML) frameworks raises significant concerns regarding human rights protection. This paper examines the ways in which AI enhances AML efforts in the banking sector, the ethical and human rights challenges that arise from its implementation, and the extent to which these strategies comply with the proportionality test under Indonesian human rights law. Using a structured document analysis of relevant regulations and secondary literature, this study finds that AI applications must respect privacy and be proportionate in addressing money laundering offences, as affirmed by the Indonesian constitution and regulatory framework. The findings highlight the urgent need for comprehensive legal frameworks to guide the development and use of AI in AML, ensuring fairness, accountability, and transparency while safeguarding human rights.